Effect of replacement different levels of flaxseed meal substitute soybean meal on some productive performance in broiler: 1-Untreated flaxseed meal. - Kesab, Yaser Ghanim Salih; AL-Shuraby, Mohammad Muhmood (Journal of Kerbala for Agricultural Sciences, 2018)
The aims of this study to know effect of replacement different levels of flaxseed meal that is 0, 15, 30, 45 and 60% substitute soybean meal on some productive performance, carcass, blood economical characteristics in broiler. A total of 80 one day old unsexed commercial broiler chicks ( Hubbard Classic) divided in randomly five treatments, in each one 16 birds kept in individual cages. This study was expand in to two periods : starter ( 1–21 ) days and grower (22-42) days. Mash diet and water were ad-libitum. The study was carried out at poultry farm in animal production department /college of agriculture and forestry / Mosul university. The results showed significant effect (p≤ 0.05) in live body weight, total weight gain, growth rate, feed conversion ratio (g feed : g weight gain) and (g feed : g carcass), water conversion ratio (mL water : g weight gain), and (mL water : g carcass), digestibility coefficient of crude protein and crude fiber, carcass weight, dressing percent, percent of thighs, wings, neck, liver, abdominal fat and pancreas. As well as on breast tenderness and juiciness, thighs tenderness, juiciness and accepility, total protein, albumin, triglycerides, HDL, LDL and vLDL Cholesterol, AST, ALT finally in uric acid. No significant effect in all other characteristics in the study. The best net return(Iraqi Dinar / Kg weight gain) for T5, T4, T3, T2 and T1 respectively. Keys words: flaxseed meal- productive performance- blood- economical- broiler.